Schools’ Perceived Readiness in Responding to Employment Policy for Person with Disability - Agustina Kustulasari; Gupita Pramahayekti; Thomas Julio Aji Setiawan (JKAP (Jurnal Kebijakan dan Administrasi Publik), 2020)
Law Number 8 of 2016 concerning Persons with disability in Indonesia has been ratified since 2016, with one of the objectives is to expand employment opportunities for persons with disabilities. This study aims to identify the schools' perceived readiness understudy in responding to the employment policy (quota of workers with disabilities of 1% for private companies and 2% for government, regional government, BUMN, and BUMD) through the implementation of vocational-based education. This study compares a number of Special Schools (SLB) and Vocational High Schools (SMK) in the Special Region of Yogyakarta to provide an overview of the perceived readiness of 2 types of schools that serve education for children with special needs. In measuring the level of perceived readiness, this research drew seven aspects: curriculum, learning process, teaching staff, management, funding, infrastructure, and environment, with an additional aspect of student input SMKs. This research is a quantitative study with a survey approach. The study found that schools perceived themselves ready, but this may be bound to their common practice and understanding of inclusive education. This study hopes to contribute to the literature and policy discussions on special education and the employment of persons with disabilities.